A Clinical Study on Jalaukavcharana Follow with Karanjadi Ghrita Dressing for the Management of Dushta Vrana w.s.r. to Non-Healing Ulcer. - Bhati , Dashrath Singh; Sharma, Vishnu Dutt (International Research Journal of Ayurveda & Yoga, 2021)
Vrana or ulcer is a very common problem encountered by medical practitioners. Sushruta Samhita, the available basic classics of Salya Tantra has given prime importance to Vrana and many chapters of the treatise are exclusively dedicated for Vrana and its management. Acharya Sushruta mentioned sixty treatment modalities for Vrana. Dushta Vrana are exhibiting less tendency or delayed tendency towards healing. It not only affects the patient physically but also the mental wellbeing of an individual. Dushta Vrana is such a long-standing ulcer with profuse discharge and slough, where removing the debris and enabling drug to reach the healthy tissue is more important. These wounds cause patients severe emotional and physical stress and create a significant financial burden on patients and the whole healthcare system. Thus, to achieve good approximation, early healing, and acceptable scar, without complications. Karanjadi Gharita was used for local application in the management of Dushta Vrana. Raktamokshan or Bloodletting tools have been dated to the Stone Age. Among the Para-surgical measures described in Ayurveda, Raktamokshan is prime important as it can provide complete remedy to many ailments. Raktamokshan using Jalauka was performed.